UNDERSTANDING THE RELATIONSHIPS OF PROGRAM SATISFACTION, PROGRAM LOYALTY AND STORE LOYALTY AMONG CARDHOLDERS OF LOYALTY PROGRAMS - Nor Asiah Omar; Norzalita Abd. Aziz; Muhamad Azrin Nazr (Asian Academy of Management Journal, 2011)
Loyalty programs have increasingly attracted interest in both academic marketing research and practice. One major factor that has been increasingly discussed is loyalty. In this study we examine the influence of cardholders’ satisfaction on loyalty (program loyalty and store loyalty) in a retail context, namely, in department stores and superstores. Data were collected from 400 cardholders of a retail loyalty program in Klang Valley, Malaysia via the drop-off and collect technique. Structural modelling techniques were applied to analyze the data. The results indicated that program satisfaction is not related to store loyalty (share-of-wallet, share-of-visit and store preference). However, loyalty to the program (program loyalty) plays a crucial intervening role in the relationship between program satisfaction and store loyalty. The study underscores the principal importance of loyalty to the program (program loyalty) in the retail loyalty program.